COMPREHENSIVE REVIEW ON THE EFFECTIVENESS OF MINDFULNESS-BASED INTERVENTIONS IN MENTAL HEALTH - 1Noor Tashtan Qlil Alzahrani, ‏2Moufaq Abduallah Sultan. AL ghamdi, 3Bashayer Siddiq Al Haddad, 4Fatima Mohammed Ahmed Kalfot, ‏5Fatmah yahya Ahmad Hamati, 6Ahmed Abdullah Alghamdy, 7Nahla Abdulrahman AL-Bana, 8Yahya Ahmed Mohammed Alawi; Bader Jeza Al Mutairi (Chelonian Research Foundation, 2022)
This review covers the existing literature on the adequacy of MBIs and highlights their effects on various populations and conditions. This audit will take a precise approach to understanding the forms that drive PTM execution, look at the methodological qualities of existing ponders, and assess suggestions for clinical use and future inquiries. This audit is planned to be coordinated to supply a more profound understanding of the utility of MBI in mental wellbeing care and to illuminate inquiries about and practice. Keywords: Mindfulness-based interventions, mental health, effectiveness, systematic review, mindfulness meditation, well-being.